Organizational Communication, Work Motivation, and Pedagogical Competence of Public Elementary School Teachers in the Division of Cabuyao City - Obispo, Rosemarie D.; Bermudo, Pedrito Jose V.; Yango, Antonio R. (Technium Social Sciences Journal, 2023)
This study attempted to determine the organizational communication, work motivation, and pedagogical competence of public elementary school teachers in the division of Cabuyao City. Specifically, it investigated the respondents’ level of organizational communication in terms of task-oriented communication and informative communication, level of work motivation in terms of intrinsic and extrinsic, and level of pedagogical competence in terms of knowledge, skills, and professional development. Further, the study probed the relationship between the respondents’ level of organizational communication and pedagogical competence, level work motivation and pedagogical competence, of, level of organizational communication and level of work motivation. Finally, it proved the predictive are level of organizational communication and level of work motivation, taken singly or in combination, of level of pedagogical competence of public elementary school teachers in the Division of Cabuyao City. The study results showed that average weighted mean of 3.60 revealed that the respondents’ level of organizational communication was very high as task oriented communication=3.60 and informative communication=3.59 were very high, an average weighted mean of 3.41 in level of work motivation was very high and revealed also that the respondents’ intrinsic =3.56 and extrinsic=3.25 were very high, and average weighted mean of 3.60 revealed the respondents’ level of pedagogical competence was very high as knowledge=3.63, skills=3.57, and professional development=3.60 were very high. The obtained p-values for task-oriented communication and =0.000 and informative communication= 0.000 were all less the level of significance of 0.01, therefore, significant relationship was observed between the level of organizational communication and level of work motivation. Likewise, the obtained p-values of knowledge, skills and professional development were 0.000 respectively were less the significance of 0.01, therefore, significant relationship was noted in the respondents’ level of organizational communication and pedagogical competence. Lastly, the obtained probability values of 0.000 (intrinsic motivation) and 0.000 (extrinsic motivation) were less the significance of 0.01, consequently, significant relationship was observed in the respondents’ level of work motivation and pedagogical competence.